Smart Mobile Augmented Reality For Orthodontics Teaching And Learning Environment - Rao Gururajaprasad, Kaggal Lakshmana (2020)
Orthodontic education, which currently employs a didactic and apprenticeship approach has been a stronghold of teacher-centric instruction. This approach is facing numerous pedagogical challenges that affect the knowledge delivery and indirectly the skill gain of students. The teaching methods affect the students at various levels leading to ineffective comprehension of underlying principles and techniques of orthodontic science. The orthodontic education which lacks a technology supported learning environment has resulted in a deficient environment for orthodontic students.